ASSESSMENT OF THE DIAGNOSTIC VALUE OF THE METHOD OF COMPUTER OLFACTOMETRY - Avrunin, Oleg; Nosova, Yana; Zlepko, Sergii; Younouss Abdelhamid , Ibrahim; Shushliapina, Nataliia (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
Olfactory studies can be a criterion for evaluating rhinosurgical intervention, and olfactory impairment may indicate respiratory impairment. Therefore, the urgent task is to develop an integrated approach to determining respiratory and olfactory disorders. A structural scheme was developed for the method of objective diagnosis of respiratory and olfactory disorders, taking into account the measu, rement of both the aerodynamic parameters of nasal breathing and the calculation of energy characteristics, which are used to determine olfactory sensitivity. The diagnostic significance of the proposed method of analyzing rhinofolipometry data with regard to additional parameters was assessed - it is necessary to take into account the time and power of breathing when the threshold of sensation of the odorivector is at the transition point of the airflow mode to the turbulent quadratic. It has been established that it is advisable to use the energy criteria of nasal breathing, pneumatic power and energy of nasal breathing under the action of the corresponding odor vector for the assessment of respiratory impaired olfactory. To assess the respiratory impairment of olfactory, it is necessary to use the method in which an odor vector is installed in the air path of the rhinomanometer, and the patient is asked to perform breathing maneuvers with a consistent increase in respiration rate while fixing the time at which olfactory sensitivity is achieved and then determining the respiratory energy characteristics. A statistical processing of diagnostic results was carried out, which confirms the adequacy of the model of independent statistical verification and makes it possible to use this method for the functional diagnosis of respiratory-olfactory disorders and testing of respiratory-olfactory sensitivity. The probability index of the error of the second kind is 0.17.